ANALYSIS OF FACTORS AFFECTING THE INCOME OF FISHERMEN IN THE COASTAL DISTRICT OF BIREM BAYEUN, EAST ACEH DISTRICT - Anggraini, Tenti; Rozalina, Rozalina; Jamil, Muhammad (AGRIBUSINESS JOURNAL, 2023)
Birem Bayeun is one of the sub-districts in East Aceh Regency with large capture fisheries production. This research aims to determine the influence of skills, knowledge, attitudes and work experience on the income of fishermen in Pesisir, Birem Bayeun District, East Aceh Regency. This research uses a causal design. The sampling technique uses the Quota Sampling method. The number of samples in this study was 42 fishermen. The data used in this research are primary and secondary data with a questionnaire measurement scale using a Likert scale. The analytical tool used is the multiple linear regression method. In conclusion, knowledge and attitudes have a significant influence on income, skills and work experience have no influence on fishermen's income.